2022
DOI: 10.24114/bss.v11i1.33852
|View full text |Cite
|
Sign up to set email alerts
|

Desain Pembelajaran Diferensiasi Bermuatan Problem Based Learning (Pbl) Mendukung Critical Thinking Skill Siswa Pada Era Kenormalan Baru Pascapandemi Covid-19

Abstract: Menjelang akhir tahun 2020, Menteri Pendidikan dan Kebudayaan Ristek RI menegaskan bahwa cita-cita pembelajaran di Indonesia ialah menciptakan pembelajaran yang berpihak kepada siswa, pembelajaran yang memerdekakan pemikiran, dan potensi siswa. Salah satu strategi yang mampu menciptakan proses pembelajaran tersebut adalah diferensiasi. Melalui artikel ini, penulis mencoba menuangkan gagasan pemikiran terkait rancangan implementasi strategi diferensiasi dalam pembelajaran bahasa Indonesia dengan muatan kemampua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
2
7
0
7
Order By: Relevance
“…Differentiated learning is an effort to adjust the learning process in the classroom in order to achieve the learning needs of each student. Through this differentiated learning, it is hoped that it can meet learning needs and develop students' creative potential so that students can solve problems and be able to think critically (Alsalhi et al, 2021;Hadi et al, 2022). This follows the results of interviews conducted with grade 4 teachers at SD N 2 Walen, which showed that this differentiated learning is carried out to meet the various needs of different students by referring to aspects of student interest, readiness and abilities possessed by students.…”
Section: Discussionsupporting
confidence: 60%
“…Differentiated learning is an effort to adjust the learning process in the classroom in order to achieve the learning needs of each student. Through this differentiated learning, it is hoped that it can meet learning needs and develop students' creative potential so that students can solve problems and be able to think critically (Alsalhi et al, 2021;Hadi et al, 2022). This follows the results of interviews conducted with grade 4 teachers at SD N 2 Walen, which showed that this differentiated learning is carried out to meet the various needs of different students by referring to aspects of student interest, readiness and abilities possessed by students.…”
Section: Discussionsupporting
confidence: 60%
“…Penelitian ini melengkapi banyak penelitian yang mengkaji pembelajaran bahasa menggunakan strategi diferensiasi dan pendekatan teknologi seperti yang dilakukan oleh (Satria & Muntaha, 2021), (Pane, Lumbantoruan & Simanjuntak, 2022), (Hadi et al, 2022), dan (Ahmadi F & Fauziya, 2023). Penelitian-penelitian ini telah berhasil memberikan alternatif yang efektif dan bermakna untuk meningkatkan pembelajaran Bahasa.…”
Section: Pembahasanunclassified
“…Salah satu tujuan pembelajaran matematika yang terdapat dalam Permendikbud No.58 tahun 2018, salah satu tujuan pembelajaran matematika di sekolah agar siswa memiliki kemampuan menjelaskan keterkaitan antar konsep dan mampu menggunakannya secara tepat dalam penyelesaian masalah. Berdasarkan uraian tersebut, tujuan pembelajaran matematika perlu dicapai dengan baik khususnya kemampuan siswa dalam memahami konsep (Hadi et al, 2022).…”
Section: Pendahuluanunclassified